Early congenital syphilis - Jihad Kassel; Hanane Baybay; Chaymae Jroundi; Sara Elloudi; Zakia Douhi; Fatima-Zahra Mernissi (Our Dermatology Online, 2022)
Syphilis is a sexually transmitted disease. Infants can become infected via transplacental transmission from an infected mother during any stage of a pregnancy. It can be associated to premature delivery, spontaneous abortion, stillbirth, nonimmune hydrops, perinatal death. Recognition of congenital syphilis is difficult because clinical presentation is diverse and often non-specific. We report a new case of early congenital syphilis.